2009
DOI: 10.1021/jp900556z
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics of Fluorene Copolymers: Control of Fluorescence and Charge Separation by the Presence of Carbazole, Oxadiazole, or Biphenyl Units

Abstract: A set of fluorene copolymers designed to introduce electron donor/acceptor structures in the polymer chain that could eventually produce more efficient charge separation with long lifetimes has been prepared. To validate our approach, herein we report photoluminescence and laser flash photolysis measurements of the series of alternating specially functionalized fluorene copolymers. The copolymers contain 9,9-dioctylfluorene and N-octylcarbazole, oxadiazole, and oxadiazole−octafluorobiphenyl−oxadiazole units. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…8,23 Oxadiazole units have been reported to affect the photophysics properties of polyfluorene-based LEDs. 24 The major color shift of in the EO-PF-DPO LEDs and LECs may be explained by charge trapping: the emission is dominated by the lowest electronic states. Further study is needed to elucidate the color shift.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,23 Oxadiazole units have been reported to affect the photophysics properties of polyfluorene-based LEDs. 24 The major color shift of in the EO-PF-DPO LEDs and LECs may be explained by charge trapping: the emission is dominated by the lowest electronic states. Further study is needed to elucidate the color shift.…”
Section: Resultsmentioning
confidence: 99%
“…White EL from a single emissive polymer has been reported in the literature by (1) covalent bonding of green and red or orange chromophores in a largely blue polymer backbone, (2) electron-trapping effect, and (3) excimer emission . In the case of polyfluorenes, both excimer or keto defects have been used to to achieve white LEDs. , Oxadiazole units have been reported to affect the photophysics properties of polyfluorene-based LEDs . The major color shift of in the EO-PF-DPO LEDs and LECs may be explained by charge trapping: the emission is dominated by the lowest electronic states.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of the polymers under study has been reported in our previous publications. , Briefly, the polymerization was done by a ring closing reaction between fluorene−ditetrazole and fluorene−dicarbonyl chloride for PFOx, and the Suzuki reactions of the corresponding oxadiazole containing dibromo-monomers with the diboronic acid monomers of fluorene, difluorene, and carbazole for PF 2 Ox, PF 3 Ox, PF 4 Ox, and PFOxCz, respectively. While PF 1 Ox, PF 3 Ox, PF 4 Ox, and PFOxCz have highly symmetric alternating structures of oxadiazole with fluorene or/and carbazole, the periodicity of PF 2 Ox is slightly low …”
Section: Resultsmentioning
confidence: 99%
“…The preparation and characterization of the fluorene copolymers has been reported previously. , UV−vis absorption spectra were recorded with a Perkin-Elmer λ35 spectrophotometer. Fluorescence spectra and lifetimes were measured on an Edinburgh Analytical Instruments FL900 spectrophotometer having a Czerny-Turner monochromator in the excitation lamp and detector photomultiplier.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation